Mise-en-Scène Strengthens Conflict in the Film God Allows Me to Sin by Hanung Bramantyo - Haditya, Reksa; Rustim (Kirana Publisher (KNPub), 2025)
This research analyzes how mise en scene, particularly setting, acting, and properties, reinforces narrative conflict in Hanung Bramantyo’s film Tuhan, Izinkan Aku Berdosa. Using a qualitative descriptive method, data were collected through repeated film observation, script analysis, documentation of key scenes, and interviews with the art director. Findings show that mise en scene elements such as narrow and dim pesantren spaces, symbolic properties like reports, phones, and hidden cameras, as well as the main actor’s emotional expressions, function as visual language that conveys tension and trauma. Properties are not mere complements but narrative triggers symbolizing oppression, manipulation, and resistance, while acting bridges the emotional depth of characters without relying on dialogue. The study concludes that mise en scene effectively intensifies both internal and external conflicts, demonstrating how Indonesian cinema communicates social and spiritual issues through visual storytelling.